Prenatal diagnosis of critical congenital heart disease reduces risk of death from cardiovascular compromise prior to planned neonatal cardiac surgery: a meta‐analysis - Holland, B. J.; Myers, J. A.; Woods, C. R. (Ultrasound in obstetrics & gynecology, 2015)
ABSTRACT Objective To determine if prenatal diagnosis improves the chance that a newborn with critical congenital heart disease will survive to undergo planned cardiac surgery. Methods A systematic review of the medical literature identified eight studies which met the following criteria: compared outcomes between newborns with prenatal and those with postnatal diagnosis of critical congenital heart disease; compared groups of patients with the same anatomical diagnosis; provided detailed information on cardiac anatomy; included detailed information on preoperative cause of death. A meta‐analysis was performed to assess differences in preoperative mortality rates between newborns with prenatal diagnosis and those with postnatal diagnosis. Patients with established risk factors for increased mortality (high risk) and those whose families chose comfort care rather than cardiac surgery were excluded. Results In patients with comparable anatomy, standard risk, a parental desire to treat and optimal care, newborns with a prenatal diagnosis of critical congenital heart disease were significantly less likely to die prior to planned cardiac surgery than were those with a comparable postnatal diagnosis (pooled odds ratio, 0.26; 95% CI, 0.08–0.84). Conclusions For newborns most likely to benefit from treatment for their critical congenital heart disease, because they did not have additional risk factors and their families pursued treatment, prenatal diagnosis reduced the risk of death prior to planned cardiac surgery relative to patients with a comparable postnatal diagnosis. Further study and efforts to improve prenatal diagnosis of congenital heart disease should therefore be considered. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd. This article has been selected for Journal Club. Click here to view slides and discussion points.